The role of hsa_circ_0008945 in juvenile-onset systemic lupus erythematosus - Qifan Wang; Baiye Xu; Qingmei Zhang; Haidao Wang; Shulian Chen; Tingting Chen; Shishan Liang (BMC, 2023)
Abstract Background circular RNAs (circRNAs) play a crucial role in many physiological and pathological processes including juvenile-onset systemic lupus erythematosus (JSLE). The aim of this study is to investigate the role of circRNA hsa_circ_0008945 in JSLE and evaluate its significance as diagnosing biomarker. Methods RT-qPCR was applied to detect the level of circ_0008945 in JSLE and controls. The Spearman correlation test assessed the correlation between circ_0008945 and clinical variables. The receiver operating characteristic (ROC) curve was calculated for evaluating the diagnostic value. Overexpression or knockdown of circ_0008945 in primary peripheral blood mononuclear cells (PBMCs) was performed to further examine its function in apoptosis. Results RT-qPCR revealed that there were significantly higher levels of hsa_circ_0008945 in PMBCs from JSLE patients (p < 0.001) compared to healthy controls. In addition, there were significant associations between hsa_circ_0008945 level and the level of C3, C4, anti-ds DNA, IgG, CRP and ESR (p < 0.05) but not associated with the level of Ig A and Ig M. ROC curve of the circ_0008945 showed that the AUC was 0.790 and it may potentially be used as a novel biomarker for the diagnosis of JSLE. The results showed that overexpression of circ-0008945 increased the apoptosis of PBMCs while knockdown of circ-0008945 by siRNA decreased the apoptosis of PBMCs, supporting that circ-0008945 promoted the apoptosis in PBMCs and contributed to the pathogenesis of JSLE. Conclusion The role of circ_0008945 was first investigated in JSLE and proposed herein their possible contribution to the pathogenesis of JSLE. This study provides not only novel insight into the pathological mechanisms but also the potential value as a useful biomarker for JSLE.